A permanent antistatic ppo / pa material and a method for producing the same

CN116178929BActive Publication Date: 2026-10-30JIANGSU HAIJU NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310094512.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-10
Publication Date
2026-10-30
Estimated Expiration
2043-02-10

AI Technical Summary

Technical Problem

但是PPO/PA合金与大多数高分子材料一样都具有良好的电绝缘性,其表面电阻率一般在1013-1015Ω.m,导电性远小于金属材料

Benefits of technology

[0016]1、本发明的抗静电剂是一种手性离子液晶,它是一种特殊的含有手性基团的液晶材料,它由阴阳离子组成。它能够很好地结合手性液晶和离子液体一些性质,离子液晶中的离子能够充当移动电荷的载流子。并且其结构还含有长烷基链,因为通过长烷基链和离子形成的斥力更容易诱导离子化合物形成液晶相。而这些长烷基链正好可以作为一个离子导电通道的绝缘层。由于离子液晶在形成液晶相时,化合物的排列方式能够实现一维或者二维上长程有序,这种长程有序的结果能够使电子在其中快速通过,非常有利于电子的快速传输和定向传输,从而实现了很好的抗静电效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004071258710000061
    Figure BDA0004071258710000061
Patent Text Reader

Abstract

The application discloses a kind of permanent antistatic PPO / PA materials and preparation method thereof.A kind of permanent antistatic PPO / PA material includes the following weight parts of raw materials: PPO 30-60 parts, PA6 20-54 parts, compatible agent 5-15 parts, chiral ionic liquid 4-10 parts, aging aid 0.1-1 part.The antistatic agent of the application is a kind of chiral ionic liquid, it is a kind of special liquid crystal material containing chiral group, it is composed of anion and cation.It can be well combined with some properties of chiral liquid crystal and ionic liquid, and the ions in ionic liquid can act as mobile charge carriers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a permanent antistatic PPO / PA material and its preparation method, belonging to the field of composite material technology. Background Technology

[0002] Polyphenylene oxide (PPO), chemically known as poly(2,6-dimethyl-1,4-phenylene ether), is widely used in machinery, office automation equipment, electronic instruments, and automobiles due to the abundant benzene ring structure in its molecular chain, which gives it high molecular chain rigidity, mechanical strength, and dimensional stability. PPO also possesses advantages such as high thermal properties, good water resistance, and low dielectric constant. However, pure PPO suffers from poor oil and solvent resistance, poor melt flowability, and difficult molding and processing, limiting its applications. Therefore, the modification of PPO is of great practical engineering significance. Among existing technologies, alloying PPO with PA is an important method for PPO modification. Nylon (PA) is a high-performance engineering plastic. Its high crystallinity makes it both solvent-resistant and wear-resistant, while also possessing good mechanical properties and excellent molding and processing performance. However, it suffers from poor heat resistance, poor dimensional stability, and low impact resistance in its finished products. Blending PA and PPO to form polymer alloys can achieve complementary advantages. It can improve the solvent resistance and processability of PPO while compensating for PA's poor high-temperature resistance and large dimensional shrinkage, thereby enhancing the stability and quality of PPO / PA products. However, like most polymer materials, PPO / PA alloys have good electrical insulation properties, with a surface resistivity typically around 10 Ω·cm. 13 -10 15 With a surface resistivity of Ω·m, its conductivity is much lower than that of metallic materials. When in contact with or rubbed against other substances, it easily generates static electricity. The negative effects of accumulated static electricity seriously affect production, daily life, and work, and can sometimes even cause fires and explosions. In certain working environments in the textile, coal mining, and electronics industries, PPO / PA alloy products are required to possess high mechanical properties, wear resistance, and other properties, as well as antistatic properties, meaning a surface resistivity of at least 10 Ω·m. 9 -10 11 Ω.m, or even 10 7 -10 8 It must be Ω.m and permanently antistatic to meet specific usage requirements. Summary of the Invention

[0003] To overcome the shortcomings of existing technologies, this invention provides a permanent antistatic PPO / PA material and its preparation method. By adding chiral ionic liquid crystals to the PPO / PA system, the antistatic effect is achieved.

[0004] This invention is achieved through the following technical solution:

[0005] A permanent antistatic PPO / PA material comprises the following raw materials in parts by weight: 30-60 parts PPO, 20-54 parts PA6, 5-15 parts compatibilizer, 4-10 parts chiral ionic liquid crystal, and 0.1-1 parts aging aid.

[0006] The aforementioned permanent antistatic PPO / PA material has a PA6 viscosity of 2.4-2.8.

[0007] The aforementioned permanent antistatic PPO / PA material has a PPO molecular weight of 20,000-30,000.

[0008] The permanent antistatic PPO / PA material is described above, wherein the compatibilizer is a mixture of PPO-g-MAH and SEBS-g-MAH in a mass ratio of 2:1.

[0009] The permanent antistatic PPO / PA material, wherein the chiral ionic liquid crystal is obtained through the following steps: ① Add 20 mL of redistilled tetrahydrofuran to a flask. The reaction apparatus needs to be in an ice bath environment. Under magnetic stirring and nitrogen protection, (S)-C2H5(CH3)C*HCH2OC6H4C6H4COOH (1.42 g, 5.00 mmol), BrC 10 H 20 COOC6H4OH (1.96 g, 5.50 mmol), dicyclohexylcarbodiimide (DCC) (1.55 g, 7.50 mmol), and 4-dimethylaminopyridine (DMAP) (61.1 mg, 0.500 mmol) were added to a round-bottom flask. The reaction environment was naturally warmed from 0 °C to room temperature, and the reaction was continued. The reaction progress was monitored by thin-layer chromatography, and the reaction was stopped when the reactants had completely reacted. The precipitate was removed by filtration, and the solvent in the reaction system was evaporated by rotary evaporation to obtain the crude product. Finally, the crude product was purified by column chromatography, recrystallized from anhydrous methanol, filtered, and dried under vacuum at 50 °C to obtain a white solid A.

[0010] ② Weigh 1.29 g (2.00 mmol) of the above white solid A into a three-necked flask, purge the air from the apparatus with nitrogen, and add 5 mL of pyridine to the reaction system under nitrogen protection. Heat the mixture to 120 °C and react for approximately 2 hours. After the reaction has cooled to room temperature, evaporate excess pyridine from the reaction system using a rotary evaporator. Dissolve the pyridine in anhydrous ethanol, and remove any remaining pyridine by rotary evaporation. Repeat this process 2-3 times. Dissolve the resulting solid in ethanol and slowly add it dropwise to a stirred container of ice-cold ether. A flocculent precipitate forms. After stirring for a period of time, place the container in a refrigerator for further recrystallization. Filter the precipitate to obtain a pale yellow solid, and dry it under vacuum at 50 °C. The product obtained is pyridine bromide.

[0011] ③ The obtained pyridine bromide was dissolved in 50 mL of deionized water by heating. An aqueous solution of potassium hexafluorophosphate (3.68 g, 20.0 mmol) was prepared and added to the reaction solution. A precipitate was observed to form. After reacting at 65 °C for 1 h, the solution was filtered and dried under vacuum. Finally, it was recrystallized with anhydrous ethanol and dried under vacuum at 50 °C to obtain a white solid B, which is the chiral ionic liquid crystal.

[0012] The permanent antistatic PPO / PA material has an ion liquid crystal melting point of 134.7℃ and a clearing point of 185℃.

[0013] The preparation method of the permanent antistatic PPO / PA material includes the following steps: first, dry mixing PPO, PA6, compatibilizer, chiral ionic liquid crystal and aging aid in a high-speed mixer for 5-8 minutes; then placing the mixed raw materials in a twin-screw extruder for melt extrusion and granulation to obtain the final ultrasonically weldable nylon.

[0014] The method for preparing a permanent antistatic PPO / PA material includes a granulation process as follows: Zone 1: 235-240℃; Zone 2: 240-245℃; Zone 3: 245-250℃; Zone 4: 250-255℃; Zone 5: 255-260℃; Zone 6: 260-270℃; Zone 7: 270-280℃; Zone 8: 280-290℃; Zone 9: 280-290℃; Zone 10: 270-280℃; residence time: 1-2 minutes; screw speed: 150-200 rpm.

[0015] The beneficial effects achieved by this invention are as follows:

[0016] 1. The antistatic agent of this invention is a chiral ionic liquid crystal, a special liquid crystal material containing chiral groups, composed of anions and cations. It effectively combines some properties of chiral liquid crystals and ionic liquids; the ions in the ionic liquid crystal can act as charge carriers for mobile charges. Furthermore, its structure contains long alkyl chains, as the repulsive force formed between the long alkyl chains and ions more easily induces the ionic compounds to form a liquid crystal phase. These long alkyl chains can also serve as an insulating layer for ion-conducting channels. Because the arrangement of compounds in the ionic liquid crystal can achieve long-range order in one or two dimensions during liquid crystal phase formation, this long-range order allows electrons to pass through rapidly, which is highly beneficial for rapid and directional electron transport, thus achieving a good antistatic effect.

[0017] 2. The chiral ionic liquid crystal used in this invention contains a benzene ring and has a similar structure to PPO. Therefore, the chiral ionic liquid crystal has good compatibility with PPO, is not easily lost, and can achieve a permanent antistatic effect.

[0018] 3. This invention uses blending modification, which has a simple preparation process, low cost, strong designability, and is easy to promote. Detailed Implementation

[0019] The present invention will now be further described. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and should not be used to limit the scope of protection of the present invention.

[0020] The materials used in this experiment require that the compatibilizer be a mixture of PPO-g-MAH and SEBS-g-MAH in a mass ratio of 2:1.

[0021] The chiral ionic liquid crystal is obtained through the following steps: ① Add 20 mL of redistilled tetrahydrofuran to a flask. The reaction apparatus needs to be in an ice bath environment. Under magnetic stirring and nitrogen protection, (S)-C2H5(CH3)C*HCH2OC6H4C6H4COOH (1.42 g, 5.00 mmol), BrC 10 H 20 COOC6H4OH (1.96 g, 5.50 mmol), dicyclohexylcarbodiimide (DCC) (1.55 g, 7.50 mmol), and 4-dimethylaminopyridine (DMAP) (61.1 mg, 0.500 mmol) were added to a round-bottom flask. The reaction environment was naturally warmed from 0 °C to room temperature, and the reaction was continued. The reaction progress was monitored by thin-layer chromatography, and the reaction was stopped when the reactants had completely reacted. The precipitate was removed by filtration, and the solvent in the reaction system was evaporated by rotary evaporation to obtain the crude product. Finally, the crude product was purified by column chromatography, recrystallized from anhydrous methanol, filtered, and dried under vacuum at 50 °C to obtain a white solid A.

[0022] ② Weigh 1.29 g (2.00 mmol) of the above white solid A into a three-necked flask, purge the air from the apparatus with nitrogen, and add 5 mL of pyridine to the reaction system under nitrogen protection. Heat the mixture to 120 °C and react for approximately 2 hours. After the reaction has cooled to room temperature, evaporate excess pyridine from the reaction system using a rotary evaporator. Dissolve the pyridine in anhydrous ethanol, and remove any remaining pyridine by rotary evaporation. Repeat this process 2-3 times. Dissolve the resulting solid in ethanol and slowly add it dropwise to a stirred container of ice-cold ether. A flocculent precipitate forms. After stirring for a period of time, place the container in a refrigerator for further recrystallization. Filter the precipitate to obtain a pale yellow solid, and dry it under vacuum at 50 °C. The product obtained is pyridine bromide.

[0023] ③ The obtained pyridine bromide was dissolved in 50 mL of deionized water by heating. An aqueous solution of potassium hexafluorophosphate (3.68 g, 20.0 mmol) was prepared and added to the reaction solution. A precipitate was observed to form. After reacting at 65 °C for 1 h, the solution was filtered and dried under vacuum. Finally, it was recrystallized with anhydrous ethanol and dried under vacuum at 50 °C to obtain a white solid B, which is the chiral ionic liquid crystal.

[0024] The specific formula and procedure for this experiment are as follows:

[0025] Example 1

[0026] 60% PPO, 20% PA6, 15% compatibilizer, 4% chiral ionic liquid crystal, and 1% aging aid are mixed evenly and then melt-extruded and granulated using a twin-screw extruder. The process is as follows: Zone 1: 235-240℃, Zone 2: 240-245℃, Zone 3: 245-250℃, Zone 4: 250-255℃, Zone 5: 255-260℃, Zone 6: 260-270℃, Zone 7: 270-280℃, Zone 8: 280-290℃, Zone 9: 280-290℃, Zone 10: 270-280℃; Residence time: 1-2 minutes; Screw speed: 150-200 rpm.

[0027] Example 2

[0028] 45% PPO, 37% PA6, 10% compatibilizer, 7% chiral ionic liquid crystal, and 1% aging aid are mixed evenly and then melt-extruded and granulated using a twin-screw extruder. The process is as follows: Zone 1: 235-240℃, Zone 2: 240-245℃, Zone 3: 245-250℃, Zone 4: 250-255℃, Zone 5: 255-260℃, Zone 6: 260-270℃, Zone 7: 270-280℃, Zone 8: 280-290℃, Zone 9: 280-290℃, Zone 10: 270-280℃; Residence time: 1-2 minutes; Screw speed: 150-200 rpm.

[0029] Example 3

[0030] 30% PPO, 54% PA6, 5% compatibilizer, 10% chiral ionic liquid crystal, and 1% aging aid are mixed evenly and then melt-extruded and granulated using a twin-screw extruder. The process is as follows: Zone 1: 235-240℃, Zone 2: 240-245℃, Zone 3: 245-250℃, Zone 4: 250-255℃, Zone 5: 255-260℃, Zone 6: 260-270℃, Zone 7: 270-280℃, Zone 8: 280-290℃, Zone 9: 280-290℃, Zone 10: 270-280℃; Residence time: 1-2 minutes; Screw speed: 150-200 rpm.

[0031] Comparative Example 1

[0032] Mix 60% PPO, 20% PA6, 19% compatibilizer, and 1% aging aid evenly, then melt-extrude and granulate using a twin-screw extruder. The process is as follows: Zone 1: 235-240℃, Zone 2: 240-245℃, Zone 3: 245-250℃, Zone 4: 250-255℃, Zone 5: 255-260℃, Zone 6: 260-270℃, Zone 7: 270-280℃, Zone 8: 280-290℃, Zone 9: 280-290℃, Zone 10: 270-280℃; residence time: 1-2 minutes; screw speed: 150-200 rpm.

[0033] Comparative Example 2

[0034] 45% PPO, 37% PA6, 17% compatibilizer, and 1% aging aid are mixed evenly and then melt-extruded and granulated using a twin-screw extruder. The process is as follows: Zone 1: 235-240℃, Zone 2: 240-245℃, Zone 3: 245-250℃, Zone 4: 250-255℃, Zone 5: 255-260℃, Zone 6: 260-270℃, Zone 7: 270-280℃, Zone 8: 280-290℃, Zone 9: 280-290℃, Zone 10: 270-280℃; Residence time: 1-2 minutes; Screw speed: 150-200 rpm.

[0035] Comparative Example 3

[0036] Mix 30% PPO, 54% PA6, 15% compatibilizer, and 1% aging aid evenly, then melt-extrude using a twin-screw extruder and granulate. The process is as follows: Zone 1: 235-240℃, Zone 2: 240-245℃, Zone 3: 245-250℃, Zone 4: 250-255℃, Zone 5: 255-260℃, Zone 6: 260-270℃, Zone 7: 270-280℃, Zone 8: 280-290℃, Zone 9: 280-290℃, Zone 10: 270-280℃; residence time: 1-2 minutes; screw speed: 150-200 rpm.

[0037] Performance evaluation methods and implementation standards:

[0038] The granulated material prepared by the above method is dried in a forced-air oven at 60°C for 2-3 hours before being injection molded on an injection molding machine.

[0039] Tensile properties were tested according to ISO 527-2, with a specimen size of 150*10*4mm and a tensile speed of 50mm / min; bending properties were tested according to ISO 178, with a specimen size of 80*10*4mm, a bending speed of 2mm / min, and a span of 64mm; impact strength of simply supported beams was tested according to ISO 179, with a specimen size of 80*6*4mm and a notch depth of one-third of the specimen thickness; the antistatic properties of the material were evaluated by the surface resistivity of the sample, with a specimen size of 150*100*3.2mm.

[0040] The formulations and performance test results of each embodiment and comparative example are shown in Table 1:

[0041] Table 1: Formulations and Material Properties of Examples 1-3 and Comparative Examples 1-3

[0042]

[0043] As shown in Table 1, comparing Examples 1-3 with Comparative Examples 1-3, the addition of chiral ionic liquid crystals significantly increases the antistatic effect of PPO / PA materials by seven orders of magnitude. Furthermore, Table 1 shows that the addition or absence of the ionic liquid crystal antistatic agent has little impact on mechanical properties, and may even slightly improve them. This is because the ionic liquid crystal material contains benzene rings, which have a structure similar to PPO, resulting in good compatibility and thus minimal impact on the material's mechanical properties. Samples 1-3 demonstrate that the impact strength, tensile strength, and flexural strength of PPO complement those of PA6, and the compatibilizer greatly expands the material's application range.

[0044] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the technical principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A permanently antistatic PPO / PA material, characterized in that, The raw materials include the following parts by weight: PPO 30-60 parts, PA6 20-54 parts, compatibilizer 5-15 parts, chiral ionic liquid crystal 4-10 parts, and aging aid 0.1-1 parts; The chiral ion liquid crystal is obtained through the following steps: ① Add 20 mL of redistilled tetrahydrofuran to a flask. The reaction apparatus should be in an ice bath environment. Under magnetic stirring and nitrogen protection, sequentially add (S)-C2H5(CH3)CHCH2OC6H4C6H4COOH and BrC 10 H 20 COOC6H4OH, dicyclohexylcarbodiimide (DCC), and 4-dimethylaminopyridine (DMAP) were added to a round-bottom flask. The reaction environment was naturally warmed from 0°C to room temperature, and the reaction was continued. The reaction progress was monitored by thin-layer chromatography. The reaction was stopped once the reactants had completely reacted. The precipitate was removed by filtration, and the solvent in the reaction system was evaporated by rotary evaporation to obtain the crude product. Finally, the crude product was purified by column chromatography, recrystallized from anhydrous methanol, and filtered to obtain a white solid A, which was dried under vacuum at 50°C. ② Weigh the above-mentioned white solid A and add it to a three-necked flask. Purge the air from the apparatus with nitrogen. Measure 5 mL of pyridine using a syringe and add it to the reaction system in the three-necked flask under nitrogen protection. Heat the mixture to 120 °C and react for about 2 hours. After the reaction cools to room temperature, evaporate the excess pyridine in the reaction system using a rotary evaporator. Dissolve the pyridine in anhydrous ethanol and remove any remaining pyridine by rotary evaporation. Repeat this process 2-3 times. Dissolve the resulting solid in ethanol and slowly add it dropwise to stirred ice-cold ether. A flocculent precipitate forms. After stirring for a period of time, place the mixture in a refrigerator for further recrystallization. Filter the precipitate to obtain a pale yellow solid. Dry the solid under vacuum at 50 °C. The product obtained is pyridine bromide. ③ The obtained pyridine bromide was added to 50 mL of deionized water and heated to dissolve. Potassium hexafluorophosphate was prepared into an aqueous solution and poured into the reaction solution. A precipitate was observed to form. After reacting at 65 °C for 1 h, the solution was filtered, dried under vacuum, and finally recrystallized with anhydrous ethanol and dried under vacuum at 50 °C to obtain white solid B, which is the chiral ionic liquid crystal.

2. The permanent antistatic PPO / PA material according to claim 1, characterized in that, The viscosity of PA6 is 2.4-2.

8.

3. The permanent antistatic PPO / PA material according to claim 2, characterized in that, The molecular weight of PPO is 20,000-30,000.

4. A permanent antistatic PPO / PA material according to claim 3, characterized in that, The compatibilizer is a mixture of PPO-g-MAH and SEBS-g-MAH in a mass ratio of 2:

1.

5. The permanent antistatic PPO / PA material according to claim 4, characterized in that, The melting point and clearing point of the ion liquid crystal are 134.7℃ and 185℃, respectively.

6. A method for preparing a permanently antistatic PPO / PA material according to any one of claims 1-5, characterized in that, Includes the following steps: First, PPO, PA6, compatibilizer, chiral ionic liquid crystal and aging aid are dry-mixed in a high-speed mixer for 5-8 minutes; the mixed raw materials are then placed in a twin-screw extruder for melt extrusion and granulation to obtain permanent antistatic PPO / PA material.

7. The method for preparing a permanent antistatic PPO / PA material according to claim 6, characterized in that, The granulation process is as follows: Zone 1: 235-240℃, Zone 2: 240-245℃, Zone 3: 245-250℃, Zone 4: 250-255℃, Zone 5: 255-260℃, Zone 6: 260-270℃, Zone 7: 270-280℃, Zone 8: 280-290℃, Zone 9: 280-290℃, Zone 10: 270-280℃; Residence time is 1-2 minutes, and screw speed is 150-200 rpm.

Citation Information

Patent Citations

  • Permanently antistatic PA66 / PPO (Polymide 6 / Poly-p-Phenylene Oxide) alloy and preparation method

    CN102399441A

  • Ion liquid crystal constructed by a positive ion Gemini surface active agent containing multiple hydroxyl groups and preparation method

    CN105367429A